Defhc1.1, a homologue of the juvenile myoclonic gene EFHC1, modulates architecture and basal activity of the neuromuscular junction in Drosophila. - Rossetto, M.G.; Zanarella, E.; Orso, G.; Scorzeto, M.; Megighian, A.; Kumar, V.; Delgado-Escueta, A.V.; Daga, A. (Human Molecular Genetics, 2011)
Mutations in the EFHC1 gene have been linked to juvenile myoclonic epilepsy. To understand EFHC1 function in vivo, we generated knockout Drosophila for the fly homolog Defhc1.1. We found that the neuromuscular junction synapse of Defhc1.1 mutants displays an increased number of satellite boutons resulting in increased spontaneous neurotransmitter release. Defhc1.1 binds to microtubules in vitro and overlaps in vivo with axonal and synaptic microtubules. Elimination of Defhc1.1 from synaptic terminals reduces the number of microtubule loops, suggesting that Defhc1.1 is a negative regulator of microtubule dynamics. In fact, pharmacological treatment of Defhc1.1 mutants with vinblastine, an inhibitor of microtubule dynamics, suppresses the satellite bouton phenotype. Furthermore, Defhc1.1 mutants display overgrowth of the dendritic arbor and Defhc1.1 overexpression reduces dendrite elaboration. These results suggest that Defhc1.1 functions as an inhibitor of neurite growth by finely tuning the microtubule cytoskeleton dynamics and that EFHC1-dependent juvenile myoclonic epilepsy may result from augmented spontaneous neurotransmitter release due to overgrowth of neuronal processes.